The Challenges of the Present and Future for a Sustainable Tourism in Albania - Doda, Sanie (Mediterranean Journal of Social Sciences, 2012)
Tourism is one of the largest and fastest growing industries in the world. It is an increasingly important source of income,employment and wealth in Albania. International tourism now accounts for a larger share of foreign exchange receipts and exportearnings than any other industry. But, while tourism provides considerable economic benefits for the country, regions andcommunities, its rapid expansion has also had detrimental environmental and socio-cultural impacts. Sustainable Tourism is acontemporary concept that is used to reflect the need of a comprehensive analysis and to consider Tourism as a need,experience and business. Anyway this shouldn’t be our single consideration. Tourism is part of overall efforts towardachievement of a sustainable Albanian Economy. The paper argues that the promotion of sustainable tourism development isessential for maximizing its socio-economic benefits and minimizing its environmental impact. It continues than with thediscussion on implementation of two instruments of sustainability such as “National Environmental Label’ and Quality Markin Albania